Entrepreneurial Transformation through the Utilization of Artificial Intelligence: Impact on Product Innovation and Business Sustainability - Maulida, Indira Shofia; Handayati, Ratna; Nurcholidah, Lilik; Lazuardi, Yanuar; Sulaeman, Moh. Muklis (PT. LITERASI SAINS NUSANTARA, 2024)
This study aims to analyze entrepreneurial transformation through the utilization of Artificial Intelligence (AI), focusing on its impact on product innovation and business sustainability. The research employs a literature review approach using qualitative methods and descriptive analysis. Data was collected from 28 journal articles published on Google Scholar between 2014 and 2024, with a rigorous selection narrowing down to 18 relevant articles for analysis. The results show that AI significantly enhances product innovation through data-driven decision-making, product personalization, and operational efficiency. Case studies from Indonesian companies such as Tokopedia, Ruangguru, and TaniHub illustrate how AI supports business sustainability through automation, risk management, and supply chain efficiency. However, AI adoption faces challenges such as limited digital literacy and resistance to change, particularly among MSMEs. The study recommends collaboration among government, academia, and industry players to create an ecosystem supporting AI adoption, enabling technology-driven entrepreneurship to thrive on a broader scale.